Are We missing out the role of oxytocin in overactive bladder syndrome?. (4th December 2020) - Canguven, Onder; Talib, Raidh
Abstract: Overactive bladder (OAB) is characterized by the storage symptoms of urgency with or without urgency incontinence. Although there is no clear cause of this idiopathic disease, overall prevalence of OAB symptoms in individuals aged 40 years old is more than 15%. Oxytocin, which is one of the most powerful contracting neuropeptide, was also shown to exhibit high intrinsic contractile activity on detrusor muscle. Oxytocin receptor antagonists that inhibit of bladder activity might offer new insights into the treatment of OAB.